Reactions of hospitalized Filipino pre-schoolers to intrusive procedure as reflected in their play behavior - Garrucho, Rosario Estrada, 1950.
The present study is focused on the following questions originally formulated by Erickson (1958) and replicated by the present investigator, regarding intrusive procedures: (1) Are 4-year-old hospitalized children able to use clinical equipment in play to express their feelings about intrusive procedures? (2) How do 4-year-old hospitalized children tend to interpret intrusive procedures? (3) What attitudes do 4-year-old hospitalized children tend to show toward personnel who administer intrusive procedures? and (4) What methods do 4-year-old hospitalized children use to cope with their feelings about intrusive procedures? In addition, hypotheses were raised along 4 general areas, namely, that (1) boys will differ from girls in play behavior, (2) hospitalized children will differ from nonhospitalized ones, (3) hospital play interviews will differ from home play interviews, and, (4) 1st play interviews will differ from subsequent ones. The study population was comprised of 3 1/2- to 4 1/2- year-old children, 28 boys and 29 girls, seen in 2 nursery schools and 3 hospitals in Quezon City in their individual homes spread out over the Metro Manila area. Included in the nonhospitalized group were 10 boys and 10 girls who had never been admitted to a hospital; they each had a school and a home (1 month later) play interview. Hospitalized group I was composed of 9 boys and 9 girls who each had 2 home interviews, 1 week and 1 month after their hospital discharge. Hospitalized group II, composed of 9 boys and 10 girls, each had 1 play interview in the hospital and 2 at home, 1 week and 1 month following discharge. Each hospitalized child selected for this study had experienced at least 1 intrusive procedure-oral, anal, or cutaneous-during his hospitalization. The study is an expose factor research in which the independent variable, intrusive procedures experienced by 4-year-old children during hospitalization had already occurred; and in which the dependent variable, the reactions of these children, as projected in their play, was observed and recorded.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Children -- Hospital care; Intrusive procedures; Play groups